Microenvironmental Heterogeneity in Brain Malignancies - Perus, Lucas J. M.; Walsh, Logan A. (Frontiers in Immunology, 2019)
Abstract Brain tumors are among the deadliest malignancies. The brain tumor microenvironment (TME) hosts a unique collection of cells, soluble factors, and extracellular matrix components that regulate disease evolution of both primary and metastatic brain malignancies. Different types of brain tumors vary widely in their microenvironmental contexture. Emerging evidence suggests an intimate link between the molecular signature of tumor cells and the composition of the TME, shedding light on the mechanisms which underlie microenvironmental heterogeneity in brain cancer. In this review, we discuss the association between TME composition, and distinct molecular profiles of primary gliomas and brain metastases, as well as the implications of the immune TME contexture on immunotherapy efficacy in brain malignancies. An appreciation for the causes and functional consequences of microenvironmental heterogeneity in brain cancer will be of crucial importance to the rational design of microenvironment-targeted therapies for these deadly diseases.